A study on the correlation between English learning styles and learning strategies of junior middle school students - He, Ruitang (Pacific International Journal, 2023)
Abstract: Researches show that learning style and learning strategy are two very important factors that affect English learning, and their mutual influence plays a role in language learning. Based On Reid's theory of perceptual learning styles and Oxford's theory of language learning strategies, this study uses the questionnaire of perceptual learning styles and language learning strategies to investigate 99 students from two classes of the second grade of a key middle school in Changchun, and interviews 12 of them.This paper explores the correlation between English learning styles and English learning strategies of junior high school students by using quantitative and qualitative methods. The results are as follows: (1) The general characteristics of junior high school students' English learning styles are that they have a variety of secondary learning styles, and only the visual style is their main learning style. (2) Junior high school students are not good at using English learning strategies, their utilization rate is low, and they lack frequently used learning strategies. (3) There are certain correlations between English learning styles and learning strategies of junior high school students, and they are all positive, but most of them are low. According to the results of the study, some suggestions are put forward for teachers and students.